Prevention of Postpartum Hemorrhage with Oxytocin versus Ergometrine Plus Oxytocin in the third stage of labor - Thitipun Nuamsiri; Kasemsis Kaewkiattikun (The Royal Thai College of Obstetricians and Gynaecologists, 2016)
Objective:To evaluate the effect of the addition of intravenous ergometrine to a standard oxytocin infusion on the blood loss during vaginal delivery.Study design: Prospective, double-blinded, randomized controlled trial.Materials and methods: Three hundred and twenty-three women were randomized to receive infusion of either ergometrine 0.2 mg plus oxytocin 20 IU or oxytocin 20 IU, diluted in 1,000 ml of 5%D/N/2, immediately after delivery of the baby. The primary outcome was the estimated blood loss. The secondary outcomes included PPH, changes in hemoglobin level, the use of additional uterotonics, need for blood transfusion and adverse effects.Results:The estimated postpartum blood loss was similar in the oxytocin-ergometrine and oxytocin groups (145 ml versus 150 ml, p=0.979). None of the women in the oxytocin-ergometrine group had PPH while one woman (0.6%) in the oxytocin group encountered this complication (p=0.498). There was no significant difference between both groups in terms of changes in hemoglobin level, use of additional uterotonics and need for blood transfusion. Hypertension was significantly more common in the oxytocin-ergometrine group than in the oxytocin group (6.2% VS 0%, p<0.001).Conclusions: There was no difference in postpartum blood loss during vaginal delivery between oxytocin-ergometrine and oxytocin groups. Hypertension was frequently found in the oxytocin-ergometrine group. However, other adverse effects were not significantly different between both groups.